Right Ventricular Hypertrophy Along With Malignant Ventricular Arrhythmias. Issue 14 (6th October 2015) - Barral, Matthias; Gandjbakhch, Estelle; Fouret, Jean-Pierre; Aubart, Fleur Cohen; Flores, Arnaud; Badenco, Nicolas; Cluzel, Philippe; Redheuil, Alban
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.